Map of North America: Engraved to Illustrate Mitchell's New Intermediate Geography. - Mitchell, S. Augustus (Samuel Augustus), 1792-1868
This map shows North and Central America and some of the surrounding areas. Countries and regions are shaded in various colors. Major cities, bodies of water, and geographic features are marked (with relief shown by hachures and spot heights as well as depth by form lines). Scale [ca. 1:34,957,000]. Prime meridians: Greenwich and Washington. The back of the map contains a page of text titled "Questions on the Map of the Eastern Hemisphere" (not included) at the top of the page and then text on the bottom half titled "The Western Hemisphere" (to the left) and "The Eastern Hemisphere" (to the right). The text in the bottom half of the page appears to be numberd facts and information regarding different regions of the world with accompanying questions in the footer.